Perbedaan Kadar Gula Darah dan Tekanan Darah Penderita Stroke Iskemik Baru dan Rekuren di RSU Haji Provinsi Sumatera Utara Tahun 2015-2016 - Ilham Kurniawan; Meizly Andina (Universitas Muhammadiyah Sumatera Utara, 2018)
Abstract: Stroke is the third leading cause of global premature death every year, in 2015 is estimated to be 6.2 million deaths caused by stroke. Furthermore, stroke is the main cause of death in vast majority hospitals through Indonesia, which is approximately 15.4%. According to Riset Basic Health 2013 survey, the prevalence of stroke has increased numerously from 8.3 per mile in 2007 to 12.1 per mile in 2013. Risk factors for stroke consist of high blood pressure and high glucose level,. The stroke patient has systolic and diastolic blood pressure of >140 mmHg and>120 mmHg, respectively. To obtain the distinction between blood-glucose level and blood pressure of acute and recurrent ischemic stroke patients at RSU Haji Province North Sumatera 2015-2016. Descriptive analytics research using medical records. The mean blood pressure of patients with acute ischemic stroke was obtained by systolic and diastolic as follows: 166,02 mmHg and 103,46 mmHg, with blood-glucose of 154,11 mmHg, by age 61-70 years at most by 28 people (16.9%) are mainly women with 44 people (26.5%). While the mean blood pressure of recurrent ischemic stroke by systolic and diastolic as follows: 165,88 mmHg and 105,28 mmHg, with blood glucose of 153,95 mmHg, with age 51-60 years by 30 people (18.1%),mainly male with the total number of 47 people (28,3%). There is no difference between blood-glucose level and blood pressure of acute and recurrent ischemic stroke patient (p>0,05).Keywords: Blood glucose, blood pressure, acute ischemic stroke,recurrent ischemic stroke.